A survey of Gallium Nitride HEMT for RF and high power applications. (September 2017) - Fletcher, A.S. Augustine; Nirmal, D.
Abstract: This paper furnishes a Comprehensive study about an emerging GaN HEMT technology suitable for RF and high power applications. It plays a vital role in Wireless communication, radars, guided missiles, and the power amplifiers in satellite communication system. Over the few decades different HEMT device structures were adopted to improve the current density and frequency performance. But it was found that AlN/GaN based HEMTs were superior in offering highest drain current of 4 A, high 2DEG charge density (ns ) of 6 × 10 13 cm −2, highest cutoff frequency of 2.02 THZ, while preserving breakdown voltages. It is because of AlN material exhibiting higher spontaneous polarization effect and large band gap energy of 6.2 eV contrast to Gallium Nitride band gap of (3.42 eV). Also, it achieves large device breakdown voltages of 2.3 kV with the help of ultra thin barrier and partial removal of local substrate. In this paper, a performance comparison between AlGaN/GaN and AlN/GaN HEMT devices were shown in detail. Different effects such as polarization, parasitic, passivation, field plate and back barrier influencing the RF and DC characteristics of Gallium Nitride based HEMTs are also included in this review. It also presents the challenges for GaN HEMT development and the issues in conventional device's technology. Highlights: A performance comparison of Various HEMT devices- GaAs, InP, GaN. The factors influencing the DC and RF characteristics of GaN HEMT technology. Important extraction models employed in GaN HEMTs. Detailed survey report on (AlN, AlGaN)/GaN based HEMT devices.